Биофизическая интерпретация методики измерения объемных данных при компьютерном планировании пластических вмешательств на лице пациента и проблемы использования этой методики - Книгавко, Ю. В.; Аврунін, О. Г. (НТУ "ХПИ", 2012)
This paper proposes an interpretation of method of biophysical changes of volume data that is used in the plastic surgery planning. Work also includes discussion of the application boundaries of this interpretation.
Keywords: Tissue Modeling and Mechanics; Plastic Surgery; computed tomography; Volume Data